Detection of pulmonary oedema by electrical impedance tomography: validation of previously proposed approaches in a clinical setting. (4th June 2019) - Zhao, Zhanqi; He, Hongli; Luo, Jingying; Adler, Andy; Zhang, Xiaoqin; Liu, Rongan; Lan, Yunping; Lu, Sen; Luo, Xiaoxiu; Lei, Yu; Frerichs, Inez; Huang, Xiaobo; et al.
Abstract: Objective : The aim of the present study was to evaluate two previously proposed approaches based on electrical impedance tomography (EIT) to assess pulmonary oedema at the bedside. Approach : Fourteen patients with acute respiratory distress syndrome were included and examined prospectively. Patients were rotated laterally along their longitudinal axis from supine to 45-degree left and right tilt to induce a gravity-dependent redistribution of pulmonary oedema. After a 20 min equilibration period at each of the three positions, 2 min EIT data were recorded and analyzed. Left-to-right lung and anterior-to-posterior ventilation ratios were calculated for each posture. The slopes of the regression lines in all three postures were then determined. The same examination was performed on the consecutive day. The EIT-derived parameters were compared with transcardiopulmonary thermodilution measurements. Main results : The correlations between the EIT and transcardiopulmonary thermodilution parameters were low (correlation coefficients r < 0.4) and not significant regardless of the examination days. Significance : Despite previous clinical and experimental observations, left-to-right and anterior-to-posterior ventilation ratios derived from EIT examinations after postural changes did not reflect total extravascular lung water in our study population. Clinical trial registration. NCT02870894 Registered 17 AUG 2016 (https://clinicaltrials.gov ).